Re-evaluating the Mimbres Region Prehispanic Chronometric Record. Issue 3 (3rd July 2017) - Anyon, Roger; Creel, Darrell; Gilman, Patricia A.; LeBlanc, Steven A.; Miller, Myles R.; Nash, Stephen E.; Nelson, Margaret C.; Putsavage, Kathryn J.; Roth, Barbara J.; Schollmeyer, Karen Gust; Sedig, Jakob W.; Turnbow, Christopher A.
Abstract : Many decades of archaeological research in the Mimbres region have resulted in hundreds of chronometric dates obtained from contexts dating prior to A.D. 1450, but until now these data have not been compiled into a single database. Using dendrochronological, radiocarbon, and archaeomagnetic dates, we analyze each of the chronometric data sets to identify patterns and biases that help us better understand the tempo and duration of fundamental transitions in the Mimbres archaeological record. We also identify critical gaps in our knowledge of the chronometric record that provide new research opportunities.